Histoire 9e - Schoeb, Suzanne; Walter, François; Cesa, Sandro; Adatte, Olivier; Audigier, François; Bugnard, Pierre-Philippe; Akkussib, André (CIIP, Conférence Intercantonale de l'Instruction Publique de la Suisse Romande et du Tessin, 2019)
Antiquité, Moyen Âge